1974
DOI: 10.1007/bf02532688
|View full text |Cite
|
Sign up to set email alerts
|

Some properties of an exocellular lipase fromRhizopus arrhizus

Abstract: Rhizopus arrhizus, a mold of the mucor family, excretes an active lipase when cultured properly. This lipase has a mol wt of 43,000 and a high carbohydrate content, Upon storage at 4C in aqueous solution, lipase I is slowly converted by proteolysis to a more cationic form, lipase II, which has a lower mol wt (32,000) and no carbohydrate.Rhizopus lipase shows the same positional specificity on long chain triglycerides as pancreatic lipase; it has no preferential side chain specificity against oleic vs. palmitic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
1

Year Published

1977
1977
1997
1997

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 22 publications
1
17
1
Order By: Relevance
“…This result suggests that the N . crassa lipase preferentially cleaves the primary ester group of triacylglycerols in the same way as pancreatic lipase (Brockerhoff & Jensen, 19746) and the lipases from Rhizopus arrhizus (Benzonana, 1974), Candida deformans (Mudherwa et al, 1985) and different Afcaligenes strains (Kokusho et al, 1982).…”
Section: Positional Specijiciy O J the Lipasementioning
confidence: 99%
“…This result suggests that the N . crassa lipase preferentially cleaves the primary ester group of triacylglycerols in the same way as pancreatic lipase (Brockerhoff & Jensen, 19746) and the lipases from Rhizopus arrhizus (Benzonana, 1974), Candida deformans (Mudherwa et al, 1985) and different Afcaligenes strains (Kokusho et al, 1982).…”
Section: Positional Specijiciy O J the Lipasementioning
confidence: 99%
“…For further enzymatic reaction, sn-1,3-dicaprin must be nonenzymatically isomerized to α,β-dicaprin. (18). Only the resulting α,β-dicaprin can be esterified to tricaprin (14,15).…”
Section: Resultsmentioning
confidence: 98%
“…Probably, the main reason for the slow reaction from dicaprin to tricaprin is that 1,3-specific lipase cannot esterify capric acid to the sn-2 position of sn-1,3-dicaprin, although sn-1,3-dicaprin was fruitfully produced. Thus, for further synthesis to tricaprin, sn-1,3-dicaprin must be isomerized to α,β-dicaprin nonenzymatically (18). This nonenzymatic isomerization must be the rate-limiting step of tricaprin synthesis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Calculations based on the percentage of protein in the total spore dry weight at the end of sporulation (60 h) indicated that 1.6 mg protein was incorporated in the spores during the sporulation process. Since extracellular enzymes have been described for R. arrhizus (Benzonana, 1974;Marshall, 1973), it was also possible that the decrease in mycelial proteins was due to the excretion of proteins into the medium. The medium protein content increased by 1.8 mg per culture from 30 to 60 h. From the above information and taking into account the amount of protein extracted from the unfractured spores, it was calculated that 12.7 yo of the protein lost during sporulation could be accounted for by means other than degradation.…”
Section: Discussionmentioning
confidence: 99%